2009
DOI: 10.1017/s0143814x0900097x
|View full text |Cite
|
Sign up to set email alerts
|

Are Aging OECD Welfare States on the Path to Gerontocracy?

Abstract: Since  the age of the average OECD median voter has increased three times faster than in the preceding  years. We use panel data from - to investigate the effects of population aging on both the program size and the benefit generosity of public pensions in  OECD countries. Population aging is accompanied by cutting smaller slices out of larger cakes: it increases aggregate spending on pensions but freezes or decreases the generosity of individual benefits. Controlling for political, institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 12 publications
1
78
1
5
Order By: Relevance
“…The more recent studies have shown, however, that the influence of party ideology has decreased over time which has been addressed to a general institutional change that took place in the early 1990s, and that can be explained by the creation of new supranational institutions, and strengthened integration of goods and capital markets (Herwartz and Theilen 2014a). Similar tendencies have been shown, for example, for health care expenditure (Potrafke 2010, Herwartz andTheilen 2014b), pension expenditure (Tepe and Vanhuysse 2009), or education expenditure (Potrafke 2011, Jensen 2011.…”
Section: Ideologymentioning
confidence: 71%
“…The more recent studies have shown, however, that the influence of party ideology has decreased over time which has been addressed to a general institutional change that took place in the early 1990s, and that can be explained by the creation of new supranational institutions, and strengthened integration of goods and capital markets (Herwartz and Theilen 2014a). Similar tendencies have been shown, for example, for health care expenditure (Potrafke 2010, Herwartz andTheilen 2014b), pension expenditure (Tepe and Vanhuysse 2009), or education expenditure (Potrafke 2011, Jensen 2011.…”
Section: Ideologymentioning
confidence: 71%
“…Most empirical studies suggest that the old-age dependency ratio has a positive effect of public spending relative to GDP 5 . However, empirical studies also show that ageing has zero or negative impact on the generosity of pensions and spending per elderly for services aimed at the elderly population (Lindert 1996;Breyer & Craig 1997;Galasso & Profeta 2004;Sanz & Velázquez 2007;Tepe & Vanhuysse 2009). Belonging to a large age group appears to be a political liability.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As a consequence, 22 On the political economy of social security see, for example, Breyer (1994) and Galasso and Profeta (2002). Over the period 1980-2002, industrialized democracies have not been dominated by distributive power of the elderly (Tepe and Vanhuysse 2009b). In any event, information increases support for pension reform (Boeri and Tabellini 2011).…”
Section: Resultsmentioning
confidence: 99%